The effect of switching protease inhibitors to raltegravir on endothelial function, in HIV-infected patients. Issue 2 (4th March 2018) - Krikke, Maaike; Tesselaar, Kiki; van den Berk, Guido E.L.; Otto, Sigrid A.; Freriks, Laura H.; van Lelyveld, Steven F.L.; Visseren, Frank J.L.; Hoepelman, Andy I.M.; Arends, Joop E.
Abstract : Objective: Lipid management is one of the cornerstones of cardiovascular risk reduction. Treatment of HIV infection with protease inhibitors (PIs) may cause dyslipidaemia, whilst the integrase inhibitor raltegravir (RAL) has a relatively favorable effect on plasma lipids. We examined the effect of switching from PIs to RAL on endothelial function, and its effect on immunological and inflammatory parameters. Methods: We performed a 16-week open-label prospective crossover study: 8 weeks intervention (switch PIs to RAL) and 8 weeks control (unchanged cART regimen). Flow-mediated dilatation (FMD), inflammatory plasma, and cellular markers of immune activation were measured at weeks 0, 8, and 16. Results: Study participants ( n  = 22) with a median age of 50 years (IQR 42–60) and known HIV infection of 6.5 years (IQR 5.0–17.3) were on stable cART with undetectable HIV viral loads. After 8 weeks of RAL therapy, a reduction in FMD of −0.81% was seen, compared to +0.54% control (pairwise, p  = 0.051), while fasting total cholesterol (−17% versus +10%; p  < 0.001), LDL cholesterol (−21% versus −3%; p  = 0.026), and triglycerides (−41% versus +18%; p  = 0.001) significantly decreased during RAL therapy compared to the control. Furthermore, a relation between the change in percentage of B-1 cells and the change in FMD was found ( β 0.40, 95%CI 0.16; 0.64, p  = 0.005) during treatment with RAL. Finally, during RAL therapy, 27% of the patients experienced an increased ALT rise. Conclusions: We present an overall negative study, where switching from PIs to RAL slightly reduced the endothelial function while decreasing plasma lipids, thus possibly decreasing the CVD risk in the long term. A transient elevation of ALT was seen upon switch to RAL.